From STEM to 4D STEM: Ultrafast Diffraction Mapping with a Hybrid-Pixel Detector. Issue 2 (12th April 2023) - Stroppa, Daniel G; Meffert, Matthias; Hoermann, Christoph; Zambon, Pietro; Bachevskaya, Darya; Remigy, Hervé; Schulze-Briese, Clemens; Piazza, Luca
Abstract: 4D scanning transmission electron microscope (STEM) techniques have been increasingly featured among the electron microscopy characterization approaches, as they provide a perspective of improved information retrieval from samples overall. To make 4D STEM experiments as viable as conventional STEM image acquisition, the recording of diffraction patterns with a pixelated detector at fast frame rates, sufficient sensitivity to capture single electron hits, and high dynamic range is necessary. This paper addresses the recent development in hybrid-pixel detector technology that now allows 4D STEM experiments with a similar setup to conventional STEM imaging with pixel collection time under 10 µs. Application examples on virtual STEM detectors and crystal phase-orientation mapping are presented.